Quantitative determination of ammonium ion in aqueous environment using riegler’s solution and artificial neural network - Tan, Ling Ling; Musa Ahmad,; Lee, Yook Heng (Universiti Kebangsaan Malaysia, 2011)
A quantitative analysis has been conducted to determine the concentration of ammonium (NH4+) ion in solution by using Ultraviolet-visible spectrophotometry method and artificial neural network (ANN). Riegler’s reagent was used to form Riegler-NH4+ complex. The characterisations of Riegler’s reagent in solution such as photostability, pH effect, reagent concentration, dynamic range and reproducibility were conducted. The colour change of the Riegler’s reagent after reaction with NH4+ was yellow to red. The Riegler’s reagent responds linearly to NH4+ ion concentration in the range of 1-7 ppm with optimum response at pH7. Satisfactory reproducibility (2.0-2.8%) were obtained with this reagent. The effect of interfering ions that may contain in the leachate on the determination of NH4+ ion was also studied. The application of ANN enabled the extension of the useful dynamic concentration range of NH4+ ion to 1–24 ppm. The best ANN architecture for Riegler-NH4+ complex was built from 29 hidden neurons, 21,389 epochs number and 0.001% learning rate which produced sum square error (SSE) value of 0.0483 with an average calibration error of 1.4136.